The Development of Integrin Alpha-8 Deficient Lungs Shows Reduced and Altered Branching and a Correction of the Phenotype During Alveolarization - Cremona, Tiziana P.; Hartner, Andrea; Schittny, Johannes C. (Frontiers in Physiology, 2020)
Lung development involves epithelial-mesenchymal interactions and integrins represent one of the key elements. These extracellular matrix receptors form hetero-dimers of alpha and beta subunits. The integrin α8β1 is highly expressed in mouse tissues, including lung. It forms a cellular receptor for fibronectin, vitronectin, osteopontin, nephronectin, and tenascin-C. This study aims to investigate the role of the integrin α8-subunit (α8) during lung development. Wild type and α8-deficient lungs were explanted at embryonic days 11.5/12.5. After 24-73 hours in culture α8-deficient lung explants displayed reduced growth, reduced branching, enlarged endbuds, altered branching patterns, and faster spontaneous contractions of the airways as compared to wild type. Postnatally, a stereological investigation revealed that lung volume, alveolar surface area, and the length of the free septal edge were significantly reduced in α8-deficient lungs at postnatal days P4 and P7. An increased formation of new septa in α8-deficient lungs rescued the phenotype. At day P90 α8-deficient lungs were comparable to wild type. We conclude that α8β1 takes not only part in the control of branching, but also possesses a morphogenic effect on the pattern and size of the future airways. Furthermore, we conclude that the phenotype observed at day P4 is caused by reduced branching and is rescued by a pronounced formation of the new septa throughout alveolarization. More studies are needed to understand the mechanism responsible for the formation of new septa in the absence of α8β1in order to be of potential therapeutic benefit for patients suffering from structural lung diseases.